"Precovery" versus recovery: Understanding the role of cherry juice in exercise recovery. (14th February 2022) - McHugh, Malachy P.
Abstract : Cherry juice has become a standard component of athlete recovery strategies. This review covers the history of cherry juice as a recovery drink to give context to its current use. Fifteen studies were identified that included a measure of muscle function, soreness, or inflammation on the days following exercise and had an exercise insult sufficient to assess the effectiveness of the tart cherry intervention. Eight studies used a concentrated juice, three used a juice from fresh‐frozen cherries, two used a tart cherry concentrate gel, and two used a tart cherry powder. The effective juice dose was specific to the type of drink (fresh‐frozen versus concentrate) but dose‐response studies are lacking, and thus, the optimal dose for any specific type of cherry juice is not known. Timing of the dosing regimen is a critical factor. Studies have uniformly shown that muscle function will recover faster on the days after exercise if juice is provided for several days prior to exercise. Effects on soreness or systemic inflammation are more equivocal. The available evidence does not support a regimen that begins on the day of exercise or post‐exercise. Tart cherry powder did not enhance any metric of recovery on the days after exercise. In conclusion, the term recovery implies an intervention that is introduced after an exercise insult. The term "precovery" may be preferable to describe interventions that should be introduced on the days prior to exercise to facilitate recovery on the days after exercise. The evidence supports cherry juice as a precovery intervention across a range of athletic activities.